Class lives : stories from across our economic divide - Collins, Chuck, 1959-; Ladd, Jennifer, 1952-; Seider, Maynard, 1943-; Yeskel, Felice (ILR Press, an imprint of Cornell University Press, 2014)
Class Lives is an anthology of narratives dramatizing the lived experience of class in America. It includes forty original essays from authors who represent a range of classes, genders, races, ethnicities, ages, and occupations across the United States. Born into poverty, working class, the middle class, and the owning class--and every place in between--the contributors describe their class journeys in narrative form, recounting one or two key stories that illustrate their growing awareness of class and their place, changing or stable, within the class system. The stories in Class Lives are both gripping and moving. One contributor grows up in hunger and as an adult becomes an advocate for the poor and homeless. Another acknowledges the truth that her working-class father's achievements afforded her and the rest of the family access to people with power. A gifted child from a working-class home soon understands that intelligence is a commodity but finds his background incompatible with his aspirations and so attempts to divide his life into separate worlds. Together, these essays form a powerful narrative about the experience of class and the importance of learning about classism, class cultures, and the intersections of class, race, and gender. Class Lives will be a helpful resource for students, teachers, sociologists, diversity trainers, activists, and a general audience. It will leave readers with an appreciation of the poignancy and power of class and the journeys that Americans grapple with on a daily basis.